Accuracy Analysis of Extraoral 3D Scanning in Dental Prosthetic - Marija Trpčić; Marija Majda Perišić; Fanika Lukačević; Stanko Škec (University of Zagreb. School of Dental Medicine, 2023)
Objective: The study has evaluated the accuracy (trueness and precision) of seven extraoral scan-ners when scanning two different types of jaws: simplified jaw with sharp edges and abutments and realistic jaw with natural teeth. The accuracies of extraoral scanners were compared, and their compliance with the required clinical accuracy levels was discussed.Material and methods: Ten scans were made with each scanner for both models. The comparison of the selected dental scanners relied on reference scans made for both models. Trueness, precision, and the distribution and value of laboratory scan points' deviations were assessed for each scanner across the models. Results: The trueness for the model of the simplified jaw with abutments ranged from 16.15 to 49.78 μm. The measured precision values for the same model ranged from 4.33 to 29.49 μm. For the model of the realistic jaw with natural teeth, the trueness results ranged from 11.32 to 24.55 μm, while the obtained precision values were between 2.29 and 18.06 μm. Conclusion: The revealed dissimilarities in the accuracies of scanners and their ranking when scanning different models lead to the conclusion that model selection is critical for the research design. All the scanners met the clinical accuracy requirements and are suitable for use in laboratories for scanning jaws with abutments and jaws with natural teeth. However, the accuracy values reported by the manufacturers of scanners are better than those obtained in this study. Furthermore, the results suggested that blue light scanners outperform white light and laser scanners.